1996
DOI: 10.1183/09031936.96.09050880
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with and accuracy of daily self-assessment of peak expiratory flows (PEF) in asthmatic subjects over a three month period

Abstract: Serial peak expiratory flow (PEF) assessment has been proposed in the clinical evaluation of asthma. In subjects attending the asthma clinic of a tertiary care hospital, we wanted to assess: 1) compliance in performing PEF; and 2) accuracy of a PEF-diary.Twenty adult asthmatic subjects, all using inhaled steroids, were asked to assess their PEF in the morning and evening with a VMX instrument (Clement Clarke Int., Colombus, OH, USA). This instrument, which incorporates a standard miniWright peak flow meter, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 24 publications
1
85
0
1
Order By: Relevance
“…Also, small but significant intercorrelations between aeroallergens and air pollutants were found in the present study ( Outcome misclassification in diary studies is an additional source of error due to a lack of truly verifiable patient data. This can occur through a lack of subject compliance (invalid PEFR maneuvers, falsified records, and distant recall), an issue that has plagued asthma diary studies to the present (39,40). Data quality could be greatly improved by the use of subnotebook diaries, nebulizer chronologs, and forced expiratory volume in 1 sec (FEV1)/PEFR monitors that are electronic and time-date stamped, but these alternatives are costly.…”
Section: Resultsmentioning
confidence: 99%
“…Also, small but significant intercorrelations between aeroallergens and air pollutants were found in the present study ( Outcome misclassification in diary studies is an additional source of error due to a lack of truly verifiable patient data. This can occur through a lack of subject compliance (invalid PEFR maneuvers, falsified records, and distant recall), an issue that has plagued asthma diary studies to the present (39,40). Data quality could be greatly improved by the use of subnotebook diaries, nebulizer chronologs, and forced expiratory volume in 1 sec (FEV1)/PEFR monitors that are electronic and time-date stamped, but these alternatives are costly.…”
Section: Resultsmentioning
confidence: 99%
“…25,29 However, our results are in striking disagreement with other studies of stable chronic asthma patients or with expert trialists, which indicated that adherence was generally poor and worsened during prolonged monitoring, and that falsification was rampant. 28,30 Also, we found that adherence was consistently higher for symptom score than for PEF (see Table 3): 82% of the patients had Ն 75% adherence with symptom score, but only 73% with PEF.…”
Section: Adherencementioning
confidence: 70%
“…Moreover, a substantial 22% of the entered values were fabricated. 28 However, the fact that the patients were clinically stable might have reduced their motivation to adhere to a method that, as in our setting, may have been perceived by patients with poorly controlled asthma as instrumental in gaining clinical improvement.…”
Section: Adherencementioning
confidence: 99%
“…In the clinical setting, several studies have shown that both occupational and nonoccupational asthmatics falsify a large percentage (20-50%) of reported measurements [45,46]. The compliance tended to decrease with time, reaching a plateau after 1 month.…”
Section: Compliancementioning
confidence: 99%